Administração intracerebroventricular de peróxido de hidrogênio: efeitos sobre a ingestão de água, excreção renal e alterações cardiovasculares induzidas por aumento da osmolaridade plasmática - Zanella, Regis Cristian (Universidade Federal de São Carlos, 2013)
The reactive oxygen species (ROS), produced endogenously in central areas may act by modulating autonomic and behavioral responses. Recent studies have shown that a reactive oxygen species, hydrogen peroxide (H2O2), injected into the lateral ventricle (LV) reduces pressor response induced by central injection of angiotensin II. In the present study we investigated the effects of H2O2 on the dipsogeni and pressor responses and on the changes in renal excretion induced by the increases in plasma osmolality by intragastric administration (ig) of 2 M NaCl (2 ml). Holtzman rats (280 - 320 g) with stainless steel cannula implanted in the LV were used. H2O2 or PBS injections were made in the LV. Injections of H2O2 (2.5 or 5 μmol/1 μl) in the LV reduced water intake induced by ig 2 M NaCl (3.1 ± 0.7 and 3.5 ± 1.1 ml, vs. PBS: 8.6 ± 1.0 and 7.6 ± 0.5 ml/2h, P <0.05, respectively) and natriuresis (609.2 ± 82.9 and 1290.7 ± 80.5, vs. PBS: 876.4 ± 129.5 and 1443.6 ± 67.5 μEq/2 h, p < 0.05, respectively). However, diuresis and pressor response after ig 2 M NaCl were not altered by the pre-treatment with H2O2. The present data suggest a inhibitory role of central H2O2 in water intake and natriuresis without changing the pressor response induced by plasma hyperosmolarity.
Intracerebroventricular administration of hydrogen peroxide: effects on water intake, renal excretion and cardiovascular changes induced by plasma hyperosmolality
Keywords: Fisiologia; Natriurese; Ratos albinos; Sede; Ocitocina; Ventrículo lateral cerebral; Ingestão de líquidos; Água; Natriuresis; Fluid intake; Rats; Thirst; Water; CIENCIAS BIOLOGICAS::FISIOLOGIA